2021
DOI: 10.1186/s13584-021-00484-8
|View full text |Cite
|
Sign up to set email alerts
|

Substances use between early and later stages of the COVID-19 pandemic in Israel

Abstract: Aims Only several empirical studies have examined substance use during the COVID-19 pandemic in general populations. Most of these studies compared self-reported substances use before the pandemic and during the pandemic's early stages. This study aims to identify the changes in substance use between the early and later waves of the COVID-19 pandemic in Israel. Methods A cross-sectional online survey recruited 750 participants (ages 18–65) in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“… 50 Fourth, the definition of the late or later COVID-19 pandemic stage was not standardized because it has ranged from three to six months after the onset of COVID-19 outbreak in other studies. 51 , 52 In Malaysia, the COVID-19 pandemic exit plan, called the “National Recovery Program,” was unveiled on 15th June 2021. 53 Following the high vaccination rates among the adult populations, coupled with the drastic reduction in the total and severe cases, Malaysia was expected to transition from the COVID-19 pandemic to an endemic phase by the end of October 2021.…”
Section: Discussionmentioning
confidence: 99%
“… 50 Fourth, the definition of the late or later COVID-19 pandemic stage was not standardized because it has ranged from three to six months after the onset of COVID-19 outbreak in other studies. 51 , 52 In Malaysia, the COVID-19 pandemic exit plan, called the “National Recovery Program,” was unveiled on 15th June 2021. 53 Following the high vaccination rates among the adult populations, coupled with the drastic reduction in the total and severe cases, Malaysia was expected to transition from the COVID-19 pandemic to an endemic phase by the end of October 2021.…”
Section: Discussionmentioning
confidence: 99%
“…The Coronavirus pandemic (COVID-19) has profoundly impacted adolescents’ lives [ 11 , 14 ]. This study examined the factors influencing risky behaviors (tobacco smoking, alcohol drinking, and drug use) among adolescents in Israel two months after the first lockdown in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The Israeli law prohibits the sale of alcoholic beverages to minors and the consumption of any alcohol by youngsters is considered dangerous and harmful, though not prohibited. As for cannabis use, the Israeli law has imposed fines on adults caught consuming cannabis for personal use, but minors are exempt from the law and treated accordingly by the welfare authorities [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, previous studies have conducted extensive population-based assessments of substance use and have demonstrated changes in substance use during the lockdown but have not reported the frequency of use in HCWs and whether these were included in the analysis. 23 , 29 , 30 That could be due to a low frequency of research framing the study of substance abuse in HCWs, as a recent review found only 3 studies on substance abuse during COVID-19, and none of these was conducted in Latin America. 31 These facts may explain the low amount and limitations of the available scientific evidence on substance use in HCWs during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%